Fabrizio Marrella / Nicola Soldati (eds.). Arbitration, Contracts and International Trade Law / Arbitrato, contratti e diritto del commercio internazionale. Essays in honor of Giorgio Bernini/ Studi in onore di Giorgio Bernini - Pretelli, Ilaria (CUADERNOS DE DERECHO TRANSNACIONAL, 2022)
This article reviews: Fabrizio Marrella / Nicola Soldati (Eds.). Arbitration, Contracts and International Trade Law / Arbitrato, contratti e diritto del commercio internazionale. Essays in honor of Giorgio Bernini/ Studi in onore di Giorgio Bernini. Milan, Giuffré-Francis Lefebvre, 2021, 683 pp.